Redefining Pregnancy-Induced Rhinitis. Issue 3 (May 2021) - Baudoin, Tomislav; Šimunjak, Tena; Bacan, Nikolina; Jelavić, Boris; Kuna, Krunoslav; Košec, Andro
Background: Pregnancy-induced rhinitis (PIR) is a form of chronic non-allergic rhinitis not present before pregnancy that manifests itself during pregnancy with complete resolution of symptoms after delivery. Objective: The objective of this ambidirectional longitudinal cohort study is to evaluate the prevalence of PIR and to investigate the appearance and character of its symptoms, and its impact on the quality of life. Methodology: Six hundred eighty-one (681) women were recruited in the study. They completed questionnaires about nasal symptoms a day after delivery and each woman with nasal symptoms was interviewed 30 days later and data on symptom duration and quality were recorded. Results: The prevalence of PIR was 31.86% (N = 217), 47.14% (N = 321) women had no nasal symptoms and 21% (N = 143) of participants had prior sinonasal disease. The clinical presentation of pregnancy rhinitis included nasal obstruction as the most common symptom, followed by rhinorrhea, postnasal secretion, nose itching, sneezing, and hyposmia. The median duration of PIR was 4 months with their complete resolution of symptoms between 2th and 16th day after delivery in the majority of respondents. PIR was diagnosed significantly more often if the women carried a female child. PIR affected their quality of life during pregnancy in 53, 9% women (N = 117), with an average VAS score of 8. It seems that pregnancy may affect the course of previously present sinonasal disease (allergic rhinitis, chronic rhinosinusitis, nonallergic rhinitis, or non-infectious rhinitis prior to the pregnancy). Conclusions: PIR is a common clinical entity with a wide range of symptoms with a direct impact on the quality of life in pregnancy. We propose a new definition of pregnancy-induced rhinitis.